Comparative studies of pure YBa2Cu3O7-ẟ prepared by modified thermal decomposition method against thermal treatment method - Mohamed Indera Alim Sah, Nur Afiqah; Awang Kechik, Mohd Mustafa; Kien, Chen Soo; Pah, Lim Kean (Springer Science and Business Media Deutschland, 2024)
High temperature superconductor Yttrium Barium Copper Oxide (YBCO) was successfully prepared by modified thermal decomposition and thermal treatment method. Both samples in that methods sintered at 980 °C and were investigate by using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and R-T measurement. From XRD analysis, it was confirmed that Yttrium Barium Copper Oxide, YBa2Cu3O7-ẟ (Y-123) acts as primary phase with orthorhombic crystal structure and Pmmm space group while Diyttrium Barium Copper Oxide, Y2BaCuO5 (Y-211) and Barium Copper Oxide (BaCuO2) belong to the secondary phases. The microstructure analysis showed that the average grain size of modified thermal decomposition (TD) method (3.6559 μm) was bigger compared with thermal treatment (TT) method (1.7766 μm). The sample exhibited metallic behavior and the critical temperature, Tc-onset was increased as modified thermal decomposition (TD) method was applied. Based on the results obtained, the modified thermal decomposition (TD) method exhibited superior performance compared to the thermal treatment (TT) in terms of the physical properties which includes microstructure, phase formation and critical temperature Tc of Y-123.